2015
DOI: 10.14411/fp.2015.063
|View full text |Cite
|
Sign up to set email alerts
|

How many species of whipworms do we share? Whipworms from man and other primates form two phylogenetic lineages

Abstract: Abstract:The whipworms, i.e. parasitic nematodes of the genus Trichuris Roederer, 1761, infect a variety of mammals. Apparently low diversity of primate-infecting species of Trichuris strongly contrasts with the high number of species described in other mammalian hosts. The present study addresses the diversity of whipworms in captive and free-ranging primates and humans by analysing nuclear (18S rRNA, ITS2) and mitochondrial (cox1) DNA. Phylogenetic analyses revealed that primate whipworms form two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 56 publications
(62 reference statements)
2
27
0
Order By: Relevance
“…Actually, occurrence of such host-shift events in Trichuris evolution has been suggested by molecular phylogenetic studies (cf. Callejón et al, 2015;Doležalová et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, occurrence of such host-shift events in Trichuris evolution has been suggested by molecular phylogenetic studies (cf. Callejón et al, 2015;Doležalová et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…60 However, in addition to the difficulty in obtaining adult worms from animals (e.g., primates), well-preserved mature nematodes are required for morphological study. 61 Hence, misidentification of the parasitic worm could result in misleading zoonotic potential of that particular parasitic worm (e.g., whipworms 61 ). Fortunately, DNA barcoding may overcome this taxonomic impediment (i.e., cryptic species).…”
Section: Importance Of Using Dna Barcoding On Sthsmentioning
confidence: 99%
“…25 However, COI gene is still not considered suitable to address phylogenetic relationships among Trichuris species because COI analysis revealed that isolates of Capillaria were found in the same clade as Trichuris. 61 This may be due to the lack of Trichuris sequences in the database. 61 For roundworms, 59 Ascaris worms were collected from 4 villages in Unguja (Africa) and the diversity of Ascaris worms based on DNA barcodes was found to be higher in Africa (15 distinct haplotypes in 59 Ascaris worms 65 compared with China [19 distinct haplotypes in 723 Ascaris worms collected from humans and pigs 66 ]).…”
Section: Importance Of Using Dna Barcoding On Sthsmentioning
confidence: 99%
See 2 more Smart Citations